Effects of Ethnicity and Spiritual Intelligence in the Relationship Between Awe and Life Satisfaction Among Chinese Primary School Teachers - Liu, Zhenhui; Li, Xin; Jin, Tonglin; Xiao, Qianguo; Wuyun, Tena (Frontiers in Psychology, 2021)
Based on the broaden-and-build theory of positive emotions, this study explored the mediating effect of spiritual intelligence between awe and life satisfaction, and whether this effect was moderated by ethnicity. Participants comprised 569 primary school teachers in Southwestern China, where many of China's ethnic minority groups reside. Awe and spiritual intelligence were found to positively predict life satisfaction, while awe also indirectly influenced life satisfaction through the partial mediation of spiritual intelligence. Ethnicity was also found to moderate the relation between awe and life satisfaction: there is a positive but non-significant relation between awe and life satisfaction in non-minority Han teachers, but a positive and significant relation between awe and life satisfaction in minority teachers. These findings not only indicate the critical role of awe in promoting life satisfaction, but also especially show that awe embodied in the traditional cultural activities makes it easier to breeds life satisfaction in minority teachers.